PARTISIPASI DALAM KERANGKA PROGRAM PEMOLISIAN MASYARAKAT MENUJU MASYARAKAT AMAN: TINJAUAN NARATIF: TINJAUAN NARATIF - Indra Pratama Putra Salmon (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2022)
The development of modernization and global dynamics basically brings a comprehensive impact on the socio-economic and cultural life of the community. In addition to being a shared goal, it also has a negative impact on society. This study uses a literature study methodology with a narrative analysis approach. The study uses data, theoretical literature, and previous studies as strengths in writing analysis. The results of the study show that technological developments have both positive and negative impacts on society, such as poverty, inequality, and other social ills. The impact was running which initially took place in urban areas, then continued in rural areas considering the trends that occurred in urban areas began to enter and develop in rural areas. On the other hand, the limitations of stakeholders (in this case the police) demand synergy with groups outside of these stakeholders, which in this case is the involvement of the community to contribute to creating stability, security and environmental order. In this regard, the community policing strategy becomes an alternative in overcoming and overcoming disturbances and threats to security and public order. The urgency and contribution of this study is that it is important to carry out community policing efforts to overcome criminal acts and even crimes in the community that can cause losses and damage in practice.